Inequality revisited: An international comparison with a special focus on the case of Germany - Judith Niehues; Maximilian Stockhausen (Institut der deutschen Wirtschaft (IW), 2021)
While global extreme poverty and global income inequality have decreased over the last decades before the Corona pandemic, inequality within many industrialized countries has increased. In Germany, net income inequality has increased after the German reunification, but since 2005 there has merely been no change in the distribution of net incomes. A similar picture can be drawn for the development of net wealth, which is generally more unequally distributed than net income. Since the end of the financial crisis, the level of net wealth inequality hast remained almost unchanged. In the last decade, both income and wealth have remarkably increased on average across all income and wealth groups. This development was accompanied by a rising share of labour income reaching levels of the 1990s again. Unfortunately, the Corona pandemic has put a temporary end to the positive income development, and it is not clear so far, what the long-run consequences of the Corona pandemic will be. In the short-run, it is especially a threat to the very poor in developing countries and it is a large challenge in the fight against global extreme poverty.
Keywords: 330